Biomechanical properties of suprapectoral biceps tenodesis with double-anchor knotless luggage tag sutures vs. subpectoral biceps tenodesis with single-anchor whipstitch suture using all-suture anchors - Richard W. Nicolay, MD; Amirhossein Jahandar, MS; Julia S. Retzky, MD; Andreas Kontaxis, PHD; Nikhil N. Verma, MD; Michael C. Fu, MD, MHS (JSES International, 2023)
Background: As the use of all-suture anchors continues to increase, limited biomechanical data on the use of these anchors in various configurations for tenodesis of the long head biceps tendon (LHBT) exists. The aim of this study was to compare the biomechanical properties of a 2-anchor luggage tag suprapectoral biceps tenodesis (Sup-BT) vs. a single-anchor whipstitch subpectoral biceps tenodesis (Sub-BT) using all-suture anchors. The hypothesis was that the Sub-BT will have a higher ultimate load to failure and less creep relative to the Sup-BT construct. Methods: Eighteen fresh frozen cadaveric humeri were used. The specimens were randomly divided into 2 groups of 9; i) The Sup-BT were performed with 2 1.8 mm knotless all-suture anchors using a luggage-tag fixation configuration, ii) The Sub-BT were performed using a single 1.9 mm all-suture anchor and a whipstitch suture configuration with a tied knot. The humeri were tested on a hydraulic MTS machine where the specimens were preloaded at 5 N for 2 minutes and then cyclically loaded from 5 to 50 N for 1000 cycles at 1 Hz while maximum displacement was recorded with a motion system and markers attached to the bone and bicep tendon. The tendon was then tensioned at a rate of 1 mm/s to obtain the ultimate load to failure. CT scans of the specimens were used to calculate the bone mineral density at the site of the anchor/bone interface and video recordings were captured during load to failure to document all modes of failure. Results: There was no significant difference in the average load to failure of the Sup-BT and Sub-BT groups (197 N ± 45 N (SD), 164 N ± 68 N (SD) respectively; P = .122) or creep under fatigue between the Sup-BT vs. Sub-BT specimens (3.1 mm, SD = 1.5 vs. 2.2 mm, SD = 0.9; P = .162). The bone mineral density was statistically different between the 2 groups (P < .001); however, there were no observed failures at the anchor/bone interface and no correlation between failure load and bone mineral density. Conclusion: The ultimate load to failure and creep between a Sup-BT with 2 knotless all-suture anchors using a luggage tag suture configuration was equivalent to a Sub-BT with 1 all-suture anchor using a whipstitched suture configuration and a tied knot. Surgeons can perform either technique confidently knowing that they are biomechanically equivalent in a cadaver model at time zero, and they offer similar strength to other fixation methods cited in the literature.